Tantangan Hukum dan Etika dalam Transplantasi Organ Manusia di Indonesia - Bakhtiar, Handina Sulastrina; Bakhtiar, Handar Subhandi (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
Human organ transplantation has become a prominent topic alongside the advancement of law and technology. Through the transplantation process, an individual may obtain an organ from another person. This study aims to examine the debate between humanitarian principles and economic considerations in the practice of organ transplantation, as well as the legal framework governing organ transplantation in Indonesia. This study is a doctrinal legal study employing conceptual and statutory approaches, and using secondary legal materials analysed qualitatively to address the central issues concerning the discourse on organ transplantation in Indonesia. The findings indicate that human organ transplantation remains ethically complex, as economic pressures and poverty often influence consent, leading to exploitation and commercialisation. Despite existing legal prohibitions, the tension between humanitarian objectives and economic necessity persists, revealing gaps in ensuring voluntary donation, fairness, and the protection of human dignity. The Government of Indonesia, through Law Number 17 of 2023 on Health (Articles 124 to 134) and Government Regulation Number 28 of 2024 (Articles 325 to 381), stipulates the procedures, medical requirements, and ethical and legal aspects of organ transplantation for humanitarian and health recovery purposes, while explicitly prohibiting any form of commercialisation.